De quelques variations contemporaines sur Madame Bovary : vers une conception énergétique de la lecture ? - Gersende Plissonneau (Flaubert: Revue Critique et Génétique)
To try to understand under what conditions could bovarysm be associated with an energetic conception of reading, we have chosen a corpus of five contemporary variations on Madame Bovary. The question we’re trying to answer implies taking into account both a heuristic redefinition of bovaryism and a more common idea of what bovayism is based on the famous definition of Jules de Gaultier. In these five texts, we thus try to study reading performances as well as dangers of reading. At another scale, our analysis also focuses on considering the reading devices of these five texts as transfictions or possible texts as defined by Escola.